An Efficient S.brunken Estimators For The Mean Of Normal Population With Kuown Variance - AI- Goburi, A. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This  article  co;nsiders a shrunken  estimator  Â·Of  Al-HermyariÂ·   andAI Gobuii (.1) to estimate  the mean (8) of a normal clistributicm N (8 cr4)  with  known variance  (cr+),  when